The Student Teams Achievement Divisions Learning Model in Its Influence on the Motivation and Science Learning Outcomes of Elementary School Students - Widdy H.F Rorimpandey; Ferawati Maaluas; Jeanne Mangangantung; Hadi Suryanto (Yayasan Keluarga Guru Mandiri, 2022)
This study aims to examine the effect of the Student Team Achievement Divisions learning model on the motivation and science learning outcomes of elementary school students. This study used an experimental research method with a non-equivalent group pretest-posttest design without a random control group. The subjects of this research were the fourth grade elementary school students, totaling 30 students. Where the experimental class amounted to 15 people and the control class amounted to 15 people. The research instruments were in the form of questionnaires and tests. The analysis technique used the independent sample t-test technique with a significance level of 0.05. The results of this study indicate First, there are differences in science learning outcomes between students who take lessons with the Student Team Achievment Divisions learning model and students who take lessons with conventional learning models. Second, there are differences in the level of motivation between students who take lessons with the Student Team Achievement Divisions learning model and students who take lessons using conventional learning models. This cooperative learning increases motivation because of the fun game by interacting with each other in the group. Third, there is a significant effect between the Student Team Achievement Divisions learning model on motivation and science learning outcomes compared to conventional lecture learning models.